Interactive effects between the invasive weed Stellera chamaejasme and grass: can arbuscular mycorrhizal fungi and fungal pathogens coregulate interspecific relationships? - Zhang, Ruohui; Qu, Shanmin; Zhang, Bin; Gao, Ying; Xing, Fu (Frontiers in Microbiology, 2023)
The interaction between poisonous weeds and neighboring plants is complex. Poisonous weeds frequently have a competitive advantage in the interaction between poisonous weeds and neighboring plants. Arbuscular mycorrhizal fungi (AMF) and plant pathogenic fungi (PPF) are closely related to the interspecific relationships of plants. However, the role of AMF and PPF between poisonous weeds and neighboring grasses remains unclear. Here, we designed a pot experiment to determine the interspecific relationship between Leymus chinensis and Stellera chamaejasme and the regulation of AMF and PPF. The results showed that interactive effects between L. chinensis and S. chamaejasme significantly inhibited the aboveground growth of both but promoted the underground growth of L. chinensis. As the proportions of S. chamaejasme increased, the total nitrogen content and pH in the rhizosphere soil of L. chinensis were reduced, the soil pH of S. chamaejasme was reduced, and the relative abundance of AMF in the rhizosphere soil of L. chinensis significantly increased and that of S. chamaejasme decreased considerably. The relative abundances of PPF in the rhizosphere soil of both in the mono-cultures were significantly higher than those in the mixed cultures. Structural equation modeling indicated that soil abiotic (pH and N availability) and biotic (AMF and PPF) factors are major drivers explaining the interactive effects between L. chinensis and S. chamaejasme. We provided new evidence for the interspecific interactions between poisonous weeds and neighboring grasses and revealed the regulatory role of AMF and PPF in the interactive effects of both plants. This study will provide a scientific basis for the prevention and control of poisonous weeds and the vegetation restoration of degraded grasslands in the future.